1983
DOI: 10.1111/j.1365-2621.1983.tb14781.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Hydrophobicity to Emulsifying Properties of Heat Denatured Proteins

Abstract: Effects of heating on the emulsifying properties of selected food proteins and the protein surface hydrophobicity (So) as a predictor of these properties were investigated. The emulsifying properties of the proteins studied were differently affected by heating. Heatdenaturation was not always accompanied by loss of emulsifying properties, but, on the contrary, in some cases resulted in great improvement. The emulsifying properties could welI be predicted solely on the basis of So level but not on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
2
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(148 citation statements)
references
References 26 publications
5
132
2
2
Order By: Relevance
“…These results agree with previous findings that both the hydrophobicity and emulsifying properties of ovalbumin could be markedly improved by heating. 18,20) Although native ovalbumin is the least hydrophobic protein,33) thermal denaturation makes this protein more amphiphilic by inducing unfolding of the molecule and exposing hydrophobic amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree with previous findings that both the hydrophobicity and emulsifying properties of ovalbumin could be markedly improved by heating. 18,20) Although native ovalbumin is the least hydrophobic protein,33) thermal denaturation makes this protein more amphiphilic by inducing unfolding of the molecule and exposing hydrophobic amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
“…Ovalbumin (Grade V). polyoxyethylene (20) sorbitan monolaurate (Tween 20). nicotinamide adenine dinucleotide (NADH).…”
Section: Methodsmentioning
confidence: 99%
“…Protein denaturation and unfolding facilitated the exposure of hydrophobic groups in gluten proteins and promote the hydrophobic interactions among them (Voutsinas et al 1983); as a result, the water absorption and gelatinization of starch granules were enhanced. Mixolab results showed that C3 and starch gelatinization rate (β) were reduced by the involved arabic gum, guar gum, or xanthan gum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the BMP used in this study was heat treated during the previous production. Excessive heat denaturation may impair the emulsifying properties by rendering the protein insoluble (Voutsinas et al, 1983). With the same BMP concentration added, emulsion Lac40 contained more aggregates than emulsion BM-MFGM40.…”
Section: +mentioning
confidence: 99%